2011
DOI: 10.1056/nejmoa1014379
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Prenatal versus Postnatal Repair of Myelomeningocele

Abstract: Background Prenatal repair of myelomeningocele, the most common form of spina bifida, may result in better neurologic function than repair deferred until after delivery. We compared outcomes of in utero repair with standard postnatal repair. Methods We randomly assigned eligible women to undergo either prenatal surgery before 26 weeks of gestation or standard postnatal repair. One primary outcome was a composite of fetal or neonatal death or the need for placement of a cerebrospinal fluid shunt by the age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

64
1,689
11
51

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,875 publications
(1,815 citation statements)
references
References 28 publications
64
1,689
11
51
Order By: Relevance
“…Por essas razões, o "National Institutes of Health (NIH)", nos EUA, patrocinou um estudo multicêntrico, prospectivo e randomizado comparando os desfechos entre as cirurgias pré-natal e pós-natal, que ficou conhecido como MOMS 33 . O estudo teve início em 2003 e foi interrompido em 2010, após recrutamento de 183 pacientes, devido à eficácia superior da cirurgia pré-natal em análise inicial.…”
Section: Ii) Correção Intrauterina De Mielomeningoceleunclassified
“…Por essas razões, o "National Institutes of Health (NIH)", nos EUA, patrocinou um estudo multicêntrico, prospectivo e randomizado comparando os desfechos entre as cirurgias pré-natal e pós-natal, que ficou conhecido como MOMS 33 . O estudo teve início em 2003 e foi interrompido em 2010, após recrutamento de 183 pacientes, devido à eficácia superior da cirurgia pré-natal em análise inicial.…”
Section: Ii) Correção Intrauterina De Mielomeningoceleunclassified
“…Although controversial, in-utero closure of the open neural tube defect may offer some advantages to the child, but the risks of preterm labor (13% delivered at less than 30 weeks gestation) and maternal health remain significant concerns. [7][8][9] An ambitious randomized trial of 183 patients has demonstrated decreased need for ventriculoperitoneal (VP) shunts, 7 as well as improved mental and motor development, decreased hind brain herniation, and improved ambulation by 30 months. 9 Urological outcomes were not part of the initial assessment, but a 2015 review of the Management of Myelomeningocele Study (MOMS) demonstrated no difference in the need for clean intermittent catheterization (CIC), but patients appeared to have less bladder trabeculation and fewer open bladder necks.…”
Section: Prenatalmentioning
confidence: 99%
“…[7][8][9] An ambitious randomized trial of 183 patients has demonstrated decreased need for ventriculoperitoneal (VP) shunts, 7 as well as improved mental and motor development, decreased hind brain herniation, and improved ambulation by 30 months. 9 Urological outcomes were not part of the initial assessment, but a 2015 review of the Management of Myelomeningocele Study (MOMS) demonstrated no difference in the need for clean intermittent catheterization (CIC), but patients appeared to have less bladder trabeculation and fewer open bladder necks. 10 The long-term implications of this are unknown, but after a review of their results, the Children's Hospital of Philadelphia declared that 18.5% of children were toilet-trained, although they did not elaborate on controls.…”
Section: Prenatalmentioning
confidence: 99%
“…Existe la hipótesis propuesta de los "dos golpes" para explicar la fisiopatología del MMC 19 . El primero estaría dado por la falla en el cierre del tubo neural con la consecuente Figura 1.…”
Section: Mielomeningoceleunclassified
“…También demostró una mejoría importante en la función neuromotora, resultando en un 42% de independencia para caminar de los pacientes del grupo de cirugía fetal, comparado con 21% del grupo control. Además demostró una ausencia de herniación del cerebro posterior en 36% en el grupo de cirugía prenatal comparado con 4% en el grupo control 19 .…”
Section: Mielomeningoceleunclassified